CONTRASTIVE ANALYSIS OF TERMINOLOGY OF THE LAW ON BILLS OF EXCHANGE AND PROMISSORY NOTES IN FRENCH AND POLISH LANGUAGES - PIEPRZYCA, Piotr (Comparative Legilinguistics, 2017)
The article presents the problem of equivalence between the main terms of the law on bills of exchange in Polish and French. First, the author presents the origins of the bill of exchange and the evolution of the law on bills of exchange from ancient times until the twentieth century when the rules concerning this branch of law were unified at the international level, in the convention concluded in Geneva on 7 June 1930. Afterwards, some terms related to bills of exchange in both language versions of the convention are analyzed in order to create the mini-dictionary of principal terms. Then these results are compared with the equivalents proposed in traditional dictionaries. The aim of this study is to check whether dictionaries are a valuable source for the translator of legal texts in relation to the corpus consisting of texts of international law, written in multiple languages.